Posthumous America : literary reinventions of America at the end of the eighteenth century - Hoffmann, Benjamin, 1985- (The Pennsylvania State University Press, 2018)
"An English translation of Benjamin Hoffmann's French monograph L'Amérique posthume. Examines the literary idealization of a lost American past in eighteenth-century French literature"--Provided by publisher.